Common variation at 3p22.1 and 7p15.3 influences multiple myeloma risk - Broderick, Peter; Weinhold, Niels; Försti, Asta; Neben, Kai; Jauch, Anna; Goldschmidt, Hartmut; Hemminki, Kari (Nature genetics, 2012)
To identify risk variants for multiple myeloma, we conducted a genome-wide association study of 1,675 individuals with multiple myeloma and 5,903 control subjects. We identified risk loci for multiple myeloma at 3p22.1 (rs1052501 in ULK4; odds ratio (OR) = 1.32; P = 7.47 × 10−9) and 7p15.3 (rs4487645, OR = 1.38; P = 3.33 × 10−15). In addition, we observed a promising association at 2p23.3 (rs6746082, OR = 1.29; P = 1.22 × 10−7). Our study identifies new genomic regions associated with multiple myeloma risk that may lead to new etiological insights.
Published: 27 November 2011
Gesehen am 07.08.2018